Evaluation of Factors Affecting Carbon Accounting Information Disclosure: A Case of ASEAN Countries - Muhammad Asif (Arthatama: Journal of Business Management and Accounting, 2021)
The study mainly investigates and evaluates the factors that influence carbon accounting information disclosure with respect to the case of ASEAN countries. The approach that is taken for collecting the data is through a primary approach where the instrument that is relevant to the research paper is the questionnaire survey. Thus, the questionnaire survey is developed on the basis of the variables that are identified from the literature, along with the utilization of the Likert scale. The sample size selected for the questionnaire collection is 425 samples, of which 385 participants have provided complete information. The SEM was utilized through the tool Smart PLS. Moreover, the path analysis results show that the governance, industry characteristics, organizational efficiency, scale of operations and transparency level have significant and positive effects on carbon accounting information disclosure. Thus, this reflects that the factors that are highly important for carbon accounting information disclosure among the ASEAN countries are governance, industry characteristics, organizational efficiency, the scale of operations, and transparency level. The qualitative study can also be incorporated to gain deep insights into the factors that are influencing CAID. Other than that, a similar approach can be undertaken among other countries such as BRIC or Middle Eastern countries.